Chemical and Biological Cyanide Destruction and Selenium Removal From Precious Metals Tailings Pond Water - R. H. Lien (The Minerals, Metals and Materials Society, 1990)
The Bureau of Mines, U. S. Department of the Interior, is investigating chemical and biological decontamination of complex wastewaters such as tailings pond water containing 280 ppm CN and 5 ppm Se as well as significant concentrations of arsenic, copper, iron, silver, and zinc. The most effective chemical procedure involves cyanide oxidation using hydrogen peroxide or sodium hypochlorite followed by selenium reduction using ferrous hydroxide. The effluent contains <l ppm CN and 20 ppb Se; concentrations of other major contaminants meet EPA drinking water standards. Preliminary research indicates that biological cyanide oxidation is possible even in highly alkaline solutions (pH 10.5) containing high cyanide concentrations; indigenous bacteria destroyed 85 pet of the cyanide. Exploratory research shows that other bacteria removed up to 79 pet of the selenium from chemically oxidized, low-cyanide water. These promising results may lead to a final processing scheme that involves a combination of chemical and biological techniques.